Application of Hydrogen Peroxide Encapsulated in Silica Xerogels to Oxidation Reactions - Dariusz Bogdał; Barbara Ryś; Szczepan Bednarz (Molecules, 2012)
Hydrogen peroxide was encapsulated into a silica xerogel matrix by the sol-gel technique. The composite was tested as an oxidizing agent both under conventional and microwave conditions in a few model reactions: Noyori’s method of octanal and 2-octanol oxidation and cycloctene epoxidation in a 1,1,1-trifluoroethanol/Na2WO4 system. The results were compared with yields obtained for reactions with 30% H2O2 and urea-hydrogen peroxide (UHP) as oxidizing agents. It was found that the composite has activity similar to 30% H2O2 and has a several advantages over UHP such as the fact that silica and H2O are the only products of the composite decomposition or no contamination by urea or its derivatives occurs; the xerogel is easier to heated by microwave irradiation than UHP and could be used as both an oxidizing agent and as solid support for microwave assisted solvent-free oxidations.